RNA2-encoded VP37 protein of Broad bean wilt virus 1 is a determinant of pathogenicity, host susceptibility, and a suppressor of post-transcriptional gene silencing - Carpino, Caterina; Ferriol, Inmaculada; Elvira-González, Laura; Medina, Vicente; Rubio, Luis; Peri, Ezio; Davino, Salvatore; Galipienso, Luis (BSPP and John Wiley & Sons Ltd., 2020)
Broad bean wilt virus 1 (BBWV-1, genus Fabavirus, family Secoviridae) is a bipartite, single-stranded positive-sense RNA virus infecting many horticultural and ornamental crops worldwide. RNA1 encodes proteins involved in viral replication whereas RNA2 encodes two coat proteins (the large and small coat proteins) and two putative movement proteins (MPs) of different sizes with overlapping C-terminal regions. In this work, we determined the role played by the small putative BBWV-1 MP (VP37) on virus pathogenicity, host specificity, and suppression of post-transcriptional gene silencing (PTGS). We engineered a BBWV-1 35S-driven full-length cDNA infectious clone corresponding to BBWV-1 RNA1 and RNA2 (pBBWV1-Wt) and generated a mutant knocking out VP37 (pBBWV1-G492C). Agroinfiltration assays showed that pBBWV1-Wt, as the original BBWV-1 isolate, infected broad bean, tomato, pepper, and Nicotiana benthamiana, whereas pBBWV1-G492C did not infect pepper and tomato systemically. Also, pBBWV1-G492C induced milder symptoms in broad bean and N. benthamiana than pBBWV1-Wt. Differential retrotranscription and amplification of the (+) and (−) strands showed that pBBWV1-G492C replicated in the agroinfiltrated leaves of pepper but not in tomato. All this suggests that VP37 is a determinant of pathogenicity and host specificity. Transient expression of VP37 through a potato virus X (PVX) vector enhanced PVX symptoms and induced systemic necrosis associated with programmed cell death in N. benthamiana plants. Finally, VP37 was identified as a viral suppressor of RNA silencing by transient expression in N. benthamiana 16c plants and movement complementation of a viral construct based on turnip crinkle virus (pTCV-GFP).